Orbital exenteration: tumour diversity and survival in a tertiary referral centre - Cumming, Benjamin; Sideris, Anders; Holmes, Timothy R.; Jacobson, Ian; Havas, Thomas (Australian Journal of Otolaryngology; Vol 2 (September 2019): Australian Journal of Otolaryngology, 2019)
Background: Orbital exenteration (OE) is performed in the context of peri-orbital or orbital malignancy, or life-threatening orbit-involving infections. The survival of patients undergoing OE for malignancy is varied in the literature. Histopathological heterogeneity has been described highlighting the complexity of orbital involving tumours. We describe our experience with OE in a metropolitan tertiary referral centre. Methods: A retrospective chart review of medical records, imaging, pathology and existing databases was performed of patients who underwent OE between January 2005 and December 2015. Disease free survival (DFS) and overall survival (OS) were calculated and Kaplan Meier survival curves generated. Subgroup analysis was performed of tumour subgroups for squamous cell carcinoma (SCC), basal cell carcinoma (BCC) and other tumour types. Results: Thirty-five orbits of 35 patients were included. Median age at OE was 69.4 years. 10 tumour types were identified. Fifteen patients underwent OE for SCC, 6 for BCC and 14 for other tumour types. Mean DFS was 64.57 months and OS was 66.81 months. There was no significant difference in survival between tumour subgroups. Conclusions: We present OE cohort data demonstrating a diverse tumour cohort, with a dominant SCC group consistent with the literature. DFS and OS in our cohort demonstrate reasonable survival outcomes. Patients requiring OE may present with a diverse range of tumour types and histopathological characteristics, highlighting the complexity of the patient with orbital involving tumours.